Astaxanthin Protects Retinal Photoreceptor Cells against High Glucose-Induced Oxidative Stress by Induction of Antioxidant Enzymes via the PI3K/Akt/Nrf2 Pathway - Tso-Ting Lai; Chung-May Yang; Chang-Hao Yang (MDPI AG, 2020)
Diabetic retinopathy (DR) is a major microvascular complication that can lead to severe visual impairment in patients with diabetes. The elevated oxidative stress and increased reactive oxygen species (ROS) production induced by hyperglycemia have been reported to play an important role in the complex pathogenesis of DR. Astaxanthin (AST), a natural carotenoid derivative, has been recently recognized as a strong free radical scavenger and might, therefore, be beneficial in different diseases, including DR. In this study, we evaluated the potential role of AST as an antioxidative and antiapoptotic agent in protecting retinal cells and also investigated the involvement of the PI3K/Akt/Nrf2 pathway in AST-mediated effects. We treated high glucose-cultured mouse photoreceptor cells (661W) with different concentrations of AST and analyzed ROS production and cell apoptosis in the different regimens. Moreover, we also analyzed the expression of PI3K, Akt, Nrf2, and Phase II enzymes after AST treatment. Our results showed that AST dose-dependently reduced ROS production and attenuated 661W cell apoptosis in a high glucose environment. Importantly, its protective effect was abolished by treatment with PI3K or Nrf2 inhibitors, indicating the involvement of the PI3K/Akt/Nrf2 pathway. These results suggest AST as a nutritional supplement that could benefit patients with DR.